Pemodelan Faktor-Faktor yang Memengaruhi Kejadian HIV/AIDS di Provinsi Jawa Barat - Taniwan, Peter; Bilbina, Ara Figura; Ganap, Christian Rafael Shalmon; Faidah, Defi Yusti (Indo-MathEdu Intellectuals Journal, 2024)
Indonesia is focusing on preparing for Indonesia’s Golden 2045 through the Golden Generation. The Golden Generation is expected to be the country's quality and superior human resource. The province of West Java, with the largest population in Indonesia, plays an important role in realizing Indonesia's Golden 2045 ambition. However, the high HIV/AIDS incidence in West Java is a major challenge that could potentially hinder Indonesia’s achievement of the 2045 Gold Plan. The Ministry of Health has launched the Three Zero HIV/AIDS concept to meet one of Indonesia's Golden 2045 pillars. Based on this, the study aims to identify factors that influence the number of HIV/AIDS cases in West Java. The HIV/AIDS case is a data count, so the approach used in this study is Poisson Regression. The results of the study showed that the number of cases of violence (X1), the percentage of use of condom contraceptives among members of the Family Planning (KB) program (X2), population density (X3), the proportion of poor population (X4), and number of health facilities per 100,000 inhabitants (X5) were related to cases of HIV/AIDS in the West Java Province. It is seen from the p-value of each variable X is 0.0 except the population density is worth 0.003. Having identified significant factors influencing cases of HIV/AIDS in West Java, the government is expected to enhance cooperation with relevant agencies in reducing the risk of the number of cases in Western Java. Thus, Three Zero in West Java can be achieved by 2030.